FLOW CYTOMETRY BASED MICRONUCLEUS ASSAY FOR EVALUATION OF GENOTOXIC POTENTIAL OF 2-ACBs IN HEPATIC CELLS HepG2 (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Food irradiation is approved for use in more than 60 countries for applications and purposes in a wide variety of foods, being an effective and safe method for preservation and long-term storage. 2-Alkylcyclobutanones (2-ACBs) are the only known radiolytic products generated from foods that contain fatty acids (Triglycerides) when irradiated. The acids analyzed in this study are palmitic and stearic, which when irradiated form 2-Dodecylcyclobutanones (2-dDCB) and 2-Tetradecylcyclobutanone (2-tDCB). Part of the 2-ACBs ingested is excreted through feces and part is deposited in adipose tissues. In vitro studies so far have been only in colon cells. The work used a human hepatoma cell line (HepG2) since the accumulation of fat in this organ is quite common. Micronucleus test was selected to evaluate possible genotoxic effects of 2-dDCB and 2-tDCB compounds when exposed to high concentrations (447, 1422 and 2235 μM) for 4 and 24 hours. Tests were performed in quadriplicates using flow cytometric analysis. None detectable genotoxic damage was observed after 4 hours of exposure to the compounds, and cytotoxic effects were only significant at the highest concentration (2235 μM) of 2-dDCB. After 24 hours of exposure, slight genotoxic damage was observed at all concentrations evaluated, and cytotoxic effects were only present when exposed to compound 2-tDCB. Although there is a genotoxic and cytotoxic effect in some of the situations tested, the two compounds predominantly induced proliferation reduction effects of this hepatic tumor cell line.